The Impact of Hsa-circ-0001947 on TGF-β Signaling in Iraqi Patients with Acute Myeloid Leukemia - Al-Asadi, Ammar Basim; Al-Saffar, Jinan M J (Iraqi Journal of Science, 2026)
Acute myeloid leukemia (AML) is a hematologic malignancy characterized by the accumulation of immature myeloid cells in the bone marrow, leading to impaired hematopoiesis. Circular RNAs (circRNAs) have emerged as key regulators in gene expression and cancer progression, including AML. This study investigates the expression of circRNA (hsa_circ_0001947) and its correlation with Transforming Growth Factor - β (TGF-β) serum levels in Iraqi AML patients. A cohort of 50 patients with AML and 40 healthy individuals was examined. The hsa_circ_0001947 expression was analyzed using quantitative RT-PCR, while serum TGF-β levels were measured using the ELISA technique. The results demonstrated a significant downregulation of hsa_circ_0001947 in AML patients compared to healthy controls (P ≤ 0.05). Additionally, AML patients exhibited significantly lower TGF-β levels (P = 0.0001), with a positive correlation (r = 0.3035, P ≤ 0.05) between hsa_circ_0001947 expression and TGF-β levels. Subgroup analysis indicated that hsa_circ_0001947 expression was lowest in newly diagnosed and relapsed AML patients compared to those undergoing treatment. These findings suggest that hsa_circ_0001947 may play a regulatory role in AML progression and could be linked to immunomodulatory mechanisms involving the TGF-β pathway. Further research is warranted to explore the molecular mechanisms underpinning hsa_circ_0001947 function in AML and its potential as a prognostic biomarker or therapeutic target.